Maternal-Neonatal Serum Albumin Level and Neonatal Respiratory Distress Syndrome in Late-Preterm Infants - Qian Ying; Xue-qin You; Fei Luo; Ji-mei Wang (Frontiers Media S.A., 2021)
Background: To determine the correlation between maternal-neonatal serum albumin level and respiratory distress syndrome (RDS) in late-preterm infants.Methods: This case-control study included 112 late-preterm newborns admitted to the neonatal intensive care unit of our hospital between January 2018 and July 2019. Those infants were divided into the RDS group (n = 56) and the non-RDS group (n = 56). Levels of maternal-neonatal serum albumin, pregnancy complications, and baseline information of the infants were compared between the two groups.Results: 1. There was no correlation between maternal and neonatal serum albumin measures. The maternal albumin level in the RDS group was lower than that in the control group (33.38 ± 3.31 vs. 33.60 ± 3.31, P > 0.05), but the difference was not statistically significant. The neonatal albumin level in the RDS group was significantly lower than that in the control group (32.70 ± 2.48 vs. 35.66 ± 3.27, P < 0.05). To predict RDS in late-preterm infants, using the albumin cutoff level of 34 g/L provides a sensitivity of 83.9% with a specificity of 62.5%. 2. Gestational age, primipara, placenta previa, antenatal corticosteroid therapy, delivery mode, and neonatal serum albumin level were associated with RDS in the late-preterm infant. 3. After adjustment for gestational age, logistic regression analysis showed that neonatal serum albumin level, placenta previa, and delivery mode were independent risk factors for RDS in late-preterm infants. However, albumin level did not related to the severity of RDS.Conclusion: The decrease in serum albumin within the first day after birth was closely related to the occurrence of RDS in late-preterm infants.